Factors Influencing the Clothing Selection and Wearing Practices of Youths in Tertiary Institutions of Abia State - A. S., Umeh-Idika (Journal of Home Economics Research, 2024)
The study determined the factors that influence the clothing selection and wearing practices of youths in tertiary institutions of Abia State. The study adopted a survey research design. Mean and t-test were used to analyze the data collected. Taro Yamen formular was used to select 396 respondents for the study. Questionnaire and the focus group discussion were used for data collection. It was revealed the various factors affected the clothing selection and wearing practices of youths in higher institutions. It was recommended that Universities should have dressing code for students. National Orientation Agency should organize seminars and workshops for the youths.